An immunoregulator nanomedicine approach for the treatment of tuberculosis - Yang, Luona; Chaves, Lee; Kutscher, Hilliard L.; Karki, Shanta; Tamblin, Maria; Kenney, Patrick; Reynolds, Jessica L. (Frontiers in Bioengineering and Biotechnology, 2023)
A nanoparticle composed of a poly(lactic-co-glycolic acid) (PLGA) core and a chitosan (CS) shell with surface-adsorbed 1,3 β-glucan (β-glucan) was synthesized. The exposure response of CS-PLGA nanoparticles (0.1 mg/ml) with surface-bound β-glucan at 0, 5, 10, 15, 20, or 25 ng or free β-glucan at 5, 10, 15, 20, or 25 ng/ml in macrophage in vitro and in vivo was investigated. In vitro studies demonstrate that gene expression for IL-1β, IL-6, and TNFα increased at 10 and 15 ng surface-bound β-glucan on CS-PLGA nanoparticles (0.1 mg/ml) and at 20 and 25 ng/ml of free β-glucan both at 24 hr and 48 hr. Secretion of TNFα protein and ROS production increased at 5, 10, 15, and 20 ng surface-bound β-glucan on CS-PLGA nanoparticles and at 20 and 25 ng/ml of free β-glucan at 24 hr. Laminarin, a Dectin-1 antagonist, prevented the increase in cytokine gene expression induced by CS-PLGA nanoparticles with surface-bound β-glucan at 10 and 15 ng, indicating a Dectin-1 receptor mechanism. Efficacy studies showed a significant reduction in intracellular accumulation of mycobacterium tuberculosis (Mtb) in monocyte-derived macrophages incubated with on CS-PLGA nanoparticles with 5, 10, and 15 ng surface-bound β-glucan or with 10 and 15 ng/ml of free β-glucan. β-glucan-CS-PLGA nanoparticles inhibited intracellular Mtb growth more than free β-glucan alone supporting the role of β-glucan-CS-PLGA nanoparticles as stronger adjuvants than free β-glucan. In vivo studies demonstrate that oral pharyngeal aspiration of CS-PLGA nanoparticles with nanogram concentrations of surface-bound β-glucan or free β-glucan increased TNFα gene expression in alveolar macrophages and TNFα protein secretion in bronchoalveolar lavage supernatants at select β-glucan concentrations. Data also demonstrate no damage to the alveolar epithelium or changes in the murine sepsis score following exposure to β-glucan-CS-PLGA nanoparticles only, indicating safety and feasibility of this nanoparticle adjuvant platform to mice by oral pharyngeal aspiration.